Comparative Analysis of Sharia Bank Financial Performance Before and After the Merger (Case Study of PT. Bank Syariah Indonesia, TBK) - Elza Sri; Ahmad Fauzul Hakim Hasibuan; Cintia Nola; Meli Anita (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
Based on Return On Assets (ROA), Return On Equity (ROE), Net Interest Margin (NIM), and Operating Expenses Against Operating Income (BOPO), the purpose of this study is to determine if there were any differences in financial performance before and after the Bank Indonesian Sharia merger. Descriptive research is used in this study, which examines the financial state of a company over time.Based on the level of explanation, this research also falls into the category of comparative research. Data that was used in the form of two years: one year prior to the merger and one year after it, came from financial reports from Bank Syariah Indonesia. Based on the average Return On Assets (ROA) reported prior to the merger, the findings of this study can be seen increase to 1.61 percent after the merger. Based on Return On Equity (ROE), the financial statements prior to the merger showed an increase of 13.71%, from an average of 10.01%. In light of the Net Interest Edge (NIM) that the budget summaries previously do a consolidation that is with a normal of 4.19% expanded later converged to 6.04%. Based on Operating Expenses vs. Operating Income (BOPO), the average of 85.63 percent in the financial statements before the merger decreased to 80.46 percent after the merger. Because there is an increase in ROA, ROE, and NIM as well as a decrease in BOPO, this study concludes that the hypothesis cannot be proven because the obtained results are not from the test but the average (mean).